Very high gravity bioethanol revisited: main challenges and advances - Gomes, Daniel Gonçalves (2021)
Over the last decades, the constant growth of the world-wide industry has been leading to more and more concerns with its direct impact on greenhouse gas (GHG) emissions. Resulting from that, rising efforts have been dedicated to a global transition from an oil-based industry to cleaner biotechnological processes. A specific example refers to the production of bioethanol to substitute the traditional transportation fuels. Bioethanol has been produced for decades now, mainly from energy crops, but more recently, also from lignocellulosic materials. Aiming to improve process economics, the fermentation of very high gravity (VHG) mediums has for long received considerable attention. Nowadays, with the growth of multi-waste valorization frameworks, VHG fermentation could be crucial for bioeconomy development. However, numerous obstacles remain. This work initially presents the main aspects of a VHG process, giving then special emphasis to some of the most important factors that traditionally affect the fermentation organism, such as nutrients depletion, osmotic stress, and ethanol toxicity. Afterwards, some factors that could possibly enable critical improvements in the future on VHG technologies are discussed. Special attention was given to the potential of the development of new fermentation organisms, nutritionally complete culture media, but also on alternative process conditions and configurations.